Interference Fading Mitigation in Coherent $Φ$ -OTDR Based on Subband Phase-Shift Transform - Yafeng Cheng; Hanyong Wang; Desheng Li; Ying Qiu; Ming Luo; Xu Zhang; Jing Zhang; Zhichao Wu; Tianye Huang; Xiang Li (IEEE Photonics Journal)
In this paper, an interference fading mitigation method based on subband phase-shift transform in coherent phase-sensitive optical time-domain reflectometer ( $Φ$ -OTDR) is proposed. The operation principle of the subband phase-shift transform with complementary amplitude characteristic is presented. The phase shift transform is performed in the digital domain without requiring complex frequency modulation. After subband phase-shift transform, the interference fading can be effectively mitigated through optimal tracking and rotated vector sum (RVS) methods. The experimental results show that the fluctuation of phase intensity is reduced from $\sim$ 70 dB to $\sim$ 20 dB and the average standard deviation of the recovered phase is also reduced from 0.223 rad to 0.046 rad. In addition, different disturbance signals are successfully recovered, verifying the effectiveness of the proposed method.